2007
DOI: 10.1111/j.1365-2303.2007.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐based endometrial cytology: cyto‐histological correlation in a population of 917 women

Abstract: Liquid-based endometrial cytology: cyto-histological correlation in a population of 917 women Objective: Liquid-based cytology, because of its capacity to reduce the obscuring factors and to provide thin-layer specimens, represents an opportunity to reevaluate endometrial cytology. In order to assess the utility of the liquid-based method in endometrial diagnosis, we evaluated its accuracy in comparison with histology. Methods: Nine hundred and seventeen women scheduled for hysteroscopy were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 36 publications
1
36
0
4
Order By: Relevance
“…The authors concluded that the tumors localized to a polyp or small area of the endometrium may go undetected by the instrument. Buccoliero et al [13] found that cytology provided sufficient material more often than biopsy, and showed the benefit of endometrial liquid-based cytology. Furthermore, a low correlation rate between D&C and Pipelle biopsy of 79% for histological diagnosis was reported in 127 cancer and noncancer patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the tumors localized to a polyp or small area of the endometrium may go undetected by the instrument. Buccoliero et al [13] found that cytology provided sufficient material more often than biopsy, and showed the benefit of endometrial liquid-based cytology. Furthermore, a low correlation rate between D&C and Pipelle biopsy of 79% for histological diagnosis was reported in 127 cancer and noncancer patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of this procedure are the reduction in confounding factors, the distribution of cells on a thin layer and the possibility to obtain more slides from the same sample. The two LBP technologies currently in use include ThinPrep (Hologic Inc., Bedford, Mass., USA) and SurePath (BD Diagnostics, Burlington, N.C., USA) and several groups have reported their experience either by using ThinPrep [10,11,14,15] or SurePath [8,9,12,13] methods. There are subtle differences between ThinPrep and SurePath preparations which reflect different sampling devices, collection media and processing techniques [20,21,22,23].…”
Section: Processing Of Endometrial Lbp Methodsmentioning
confidence: 99%
“…In fact, the LBP method enables storage of a variable amount of cells. Recently, several studies have described the cellular assessment of endometrial lesions by using cytoarchitectural criteria on LBPs [8,9,10,11,12,13,14,15]. The above described advantages of LBPs versus conventional slides suggest the replacement of conventional slides with LBPs in the routine cytologic evaluation of endometrial cell samples.…”
Section: Introductionmentioning
confidence: 99%
“…Because the sensitivity and specificity of TVS were 97.4 and 75.7%, respectively, they concluded that TVS was more useful in identifying patients who required further diagnostic investigation, including endometrial histology. Buccoliero et al [7] studied 917 patients who were scheduled for hysterectomy with the liquid-based cytology method. All the women proceeded sequentially through hysteroscopy, endometrial cytology and endometrial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…According to their study, cytology provided more sufficient information than biopsy; sensitivity and specificity were 96 and 98%, respectively, PPV was 86% and NPV was 99%. In addition, several studies have mentioned the sensitivity and specificity of endometrial cytology [7,8,9]. In these studies, cytologically ‘positive’ was also determined for the first time.…”
Section: Discussionmentioning
confidence: 99%